GAMBARAN PENDONOR DARAH DI UTD PMI KABUPATEN BANTUL TAHUN 2020 - Atik Dina Naseha; Nur’Aini Purnamaningsih; Kuswanto Hardjo (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
At the end of 2019, it was found that there was a very fast mutating virus called the Covid-19 virus, this virus causes diseases ranging from coughs to colds to death, efforts to prevent the spread of this virus by limiting the social scale of the community which causes a decrease in the number of blood donors which has an impact on the amount of blood stock in Blood Donation Unit. The objective of this study was to determine the description of blood donors based on blood type, gender, age, and type of donor at Blood Donation Unit Bantul Regency in 2020. This study was an activity report by observing secondary data obtained from Blood Donation Unit Bantul Regency. The number of donors was 8.212 donors, of which the number of donations from inside the building was 5.936 donors (72,28%), and the number of donations from mobile units was 2.276 donors (27,72%). The results showed that the majority of blood donors were blood group 0, which was 3.506 (42,69%), and the least blood type was AB, which was 468 (5.70%). The majority of the gender of the donor was male, namely 7.020 (85,48%), for female, 1.192 (14,52%). The majority of donors are aged 17-24 years, namely 1.738 (21,16%), and at least 65 years old 45 (0,55%). The majority of voluntary donors were 5.151 (62,73%), and the subtitute/ family donors were 1.034 (12,59%). There were 8.212 blood donors where the majority of blood group 0 was 3.506 (42,69%), male sex was 7.020 (85,48%), in the 17-24 year age group 1.738 (21,16%), and repeated voluntary donors were 5.151 (62,73%).